2013
DOI: 10.1073/pnas.1219813110
|View full text |Cite
|
Sign up to set email alerts
|

Shaping organs by a wingless-int/Notch/nonmuscle myosin module which orients feather bud elongation

Abstract: How organs are shaped to specific forms is a fundamental issue in developmental biology. To address this question, we used the repetitive, periodic pattern of feather morphogenesis on chicken skin as a model. Avian feathers within a single tract extend from dome-shaped primordia to thin conical structures with a common axis of orientation. From a systems biology perspective, the process is precise and robust. Using tissue transplantation assays, we demonstrate that a "zone of polarizing activity," localized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 57 publications
5
51
0
Order By: Relevance
“…In biology, where networks of cells arise naturally, the Turing model remains controversial because comparison of experiment and theory is hampered by incomplete knowledge of the morphogens involved in development, the rate constants of the reactions, the mechanisms of intercellular coupling, and the role of elasticity (5,7,15,16).…”
mentioning
confidence: 99%
“…In biology, where networks of cells arise naturally, the Turing model remains controversial because comparison of experiment and theory is hampered by incomplete knowledge of the morphogens involved in development, the rate constants of the reactions, the mechanisms of intercellular coupling, and the role of elasticity (5,7,15,16).…”
mentioning
confidence: 99%
“…Meanwhile, the nuclear β-catenin signaling elevates expression of Jag1, which binds to Notch receptors on neighboring cells, generating a local positive feedback to demarcate the boundaries of the nuclear β-catenin zone. This interaction guarantees the precision of feather bud elongation orientation (33). It is interesting that Hex/Prh shows an expression pattern similar to that of Wnt-7a (34).…”
Section: Development Of Feather Budsmentioning
confidence: 95%
“…miRNAs function as posttranscriptional regulators by binding to the 3′ untranslated region of target mRNAs to repress translation or to cleave mRNAs. Recently, Zhang et al (51) showed that, based on the bioinformatic data, seven miRNAs collected from the follicles of growing contour and down feathers may target the genes of Wnt/β-catenin, Shh/BMP, and Notch pathways, which are important for feather morphogenesis (33, 48, 52). The differential expression profile between these two feather types was shown, suggesting the presence of a new category of molecular control, although functional data remain to be demonstrated.…”
Section: Feather Follicle: Regeneration and Morphogenesismentioning
confidence: 99%
“…A notable recent example combines kinetic and mechanics approaches to demonstrate oscillations of myosin contractile activity in the observed spatiotemporal pattern in the elongating Drosophila egg chamber [47]. Potential topics for mechanochemical modeling include a wingless-int chemical gradient specifying the precise domains of localized nonmuscle myosin II activity during chick feather morphogenesis [48] and feedback between ROCK and Shroom signaling to amplify planar polarized actomyosin contractility during Drosophila germband extension [49]. It will also be interesting to incorporate more complex feedback between intercellular forces and cellular biochemistry.…”
Section: Outlook and Concluding Remarksmentioning
confidence: 99%